2019
DOI: 10.1007/s12185-019-02715-w
|View full text |Cite
|
Sign up to set email alerts
|

Real-world data on the efficacy and safety of daratumumab treatment in Hungarian relapsed/refractory multiple myeloma patients

Abstract: Daratumumab is a human anti-CD38 monoclonal antibody used in the treatment of refractory and relapsed multiple myeloma. We investigated the efficacy and safety of daratumumab therapy in a real-world setting. Ninety-nine Hungarian patients were included; 48 received monotherapy, while lenalidomide and bortezomib combinations were administered in 29 and 19 cases, respectively. Overall response rate was assessable in 88 patients, with 12 complete, 10 very good partial, 34 partial, and seven minor responses. At a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 14 publications
2
29
0
2
Order By: Relevance
“…3 A pooled analysis of these monotherapy studies showed an overall response rate (ORR) of 31.1%, median progression-free survival (PFS) of 4.0 months, median overall survival (OS) of 20.1 months, and a manageable toxicity profile for patients treated with daratumumab at 16 mg/kg. 10 The efficacy and favorable tolerability of daratumumab monotherapy has been consistently reported from recent real-world studies performed in countries such as the United States, Korea, Poland, Spain, Italy, Russia, the United Kingdom, Hungary, and Japan, with the ORR ranging from 23% to 56.3% [11][12][13][14][15][16][17] ( Table 1).…”
Section: Introductionmentioning
confidence: 66%
See 3 more Smart Citations
“…3 A pooled analysis of these monotherapy studies showed an overall response rate (ORR) of 31.1%, median progression-free survival (PFS) of 4.0 months, median overall survival (OS) of 20.1 months, and a manageable toxicity profile for patients treated with daratumumab at 16 mg/kg. 10 The efficacy and favorable tolerability of daratumumab monotherapy has been consistently reported from recent real-world studies performed in countries such as the United States, Korea, Poland, Spain, Italy, Russia, the United Kingdom, Hungary, and Japan, with the ORR ranging from 23% to 56.3% [11][12][13][14][15][16][17] ( Table 1).…”
Section: Introductionmentioning
confidence: 66%
“…Salomon-Perzy nski et al 13 Cejalvo et al 14 Cook et al 15 Lovas et al 16 Iida et al 17 Present Study (Turkish Cohort)…”
Section: Characteristicmentioning
confidence: 86%
See 2 more Smart Citations
“…Lovas et al investigated daratumumab therapy in 99 patients with RRMM in a real-world setting (48 as a single agent, 29 and 19 cases in combination with lenalidomide and bortezomib, respectively) [46]. Among 88 evaluable patients, 12 achieved CR, 10 VGPR, and 34 PR.…”
Section: Other Daratumumab Multiagent Associations and Combinations Wmentioning
confidence: 99%